Nuclear Medicine Methods for Assessment of Chronic Chagas Heart Disease - Simões,Marcus Vinicius (2020)
Abstract Several different imaging methods can be used to evaluate patients with Chagas heart disease (CHD) for diagnostic and prognostic purposes, including plain chest radiography; echocardiography; myocardial perfusion scintigraphy, for detection of ischemia and fibrosis; radionuclide gated-angiography, for evaluation of biventricular function; 123I-MIBG labeling of sympathetic myocardial innervation; MRI, for detection and quantitation of myocardial fibrosis; and coronary angiography. This study aims to review the contributions of these nuclear medicine methods to understanding of the pathophysiology of chronic Chagas cardiomyopathy (CCC). Careful analysis and integration of findings provided by these imaging methods in patients with CCC at different stages has contributed significantly to improving understanding of several peculiarities of the disease. Clinical and experimental studies in animal models show that perfusion abnormalities detected in association with dysfunctional but viable myocardium are a common finding in CCC patients and correspond to areas of cardiac sympathetic denervation, as assessed by 123I-MIBG imaging. Furthermore, recent reports have demonstrated a close relationship between coronary microvascular disturbances and myocardial inflammation. Thus, ongoing research, mainly focused on refinements of 18F-FDF -PET techniques and further exploration of nuclear methods, such as SPECT, have the potential to contribute to detection and monitoring of early subclinical myocardial damage thereby enabling evaluation of therapeutic strategies targeting inflammation and microvascular ischemia that could result in better prognostic stratification of patients with CHD.